PERUBAHAN KEMAMPUAN KOMUNIKASI VERBAL SISWA KELAS VIIC SMP N 3 KESUGIHAN CILACAP DALAM MENGGUNAKAN BAHASA INDONESIA YANG BAKU - Latif Junaedi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
At this time many students in junior (SMP) to senior high school (SMA) is less interested and motivated in using the Indonesian language is right and good. This is because widespread notion that slang and jargon that is considered better, coolier and easier to do, regardless of the grammar used. This has an impact on the development of Indonesian language is less good. The impact of proficiency level also occurs during the process of learning Indonesian language in the classroom VIIC SMP Negeri 3 Kesugihan Cilacap. Ability to communicate students SMP Negeri 3 Kesugihan Cilacap using the Indonesian language is good and right to have an average value which is still below the completeness criteria (56.48). This condition also affects the value of the UN, that the bulk of the lack of graduates in subjects Indonesian language. The purpose of the research include: determine the ability to communicate, use of grammar and vocabulary by each student is good and right according to the Indonesian language and the correct standard. The study was conducted using action research methods in class VIIC SMP Negeri 3. Kesugihan Cilacap. Data collection techniques used were student presentations, and writing a story-based narrative. The results showed the two cycles average score value of word usage = 73.4; phrase = 74.4; clause = 76.8; and value of syntax = 80.8. In cycle 2 (stage 2) results of portfolio assessment (manuscript presentation) students' average scores increased value, namely 74.3 (use of the word), 75.5 (phrase); 78.3 (clause) and 80.5 (syntax). In cycle 1 in the assessment of verbal ability shows the average scores: 71.4 (volume/voice), 73.1 (intonation), 75.7 (articulation) and 80.8 (expression). The average score value of verbal communication skills of students in cycle 2 (stage 2) increases with the value: 73.7 (volume / voice), 74.7 (intonation), 76.8 (articulation), and 82.8 (expression). Thus, changes in students' skills verbal communication SMP N 3 Kesugihan high enough using the standards of Indonesian language. Keywords: Changes of skills verbal communication, Indonesian language, portfolio